Anti-inflammatory effect of aged black garlic on 12-O-tetradecanoylphorbol-13-acetate-induced dermatitis in mice - You, Bo Ram (Nutr Res Pract, 2019)
BACKGROUND/OBJECTIVES: Although aged black garlic has various biological activities such as anti-allergy, anti-inflammation and neuroprotection, effect of aged black garlic on chemically contact dermatitis is unclarified. MATERIALS/METHODS: To evaluate anti-dermatitic activity of aged black garlic extract, we investigated effects of a fraction of aged black garlic extract (BG10) on both in vivo and in vitro. RESULTS: BG10 almost inhibited formation of nitric monoxide and interleukin-6 (IL-6; IC(50), 7.07 µg/mL) at 25 µg/mL, and dose-dependently reduced production of tumor necrosis factor-α (TNF-α; IC(50), 52.07 µg/mL) and prostaglandin E(2) (IC(50), 38.46 µg/mL) in lipopolysaccharide-stimulated RAW264.7 cells. In addition, BG10 significantly inhibited the expression of inducible nitric oxide synthase, cyclooxygenase-2 and nuclear NF-κB, and improved that of cytosolic levels of NF-κB and IκBα in the cells. Consistent with in vitro studies, BG10 (0.5 mg/mL) not only reduced ear edema but also suppressed the formation of IL-6 and TNF-α induced by 12-O-tetradecanoylphorbol-13-acetate in ear tissues of mice. CONCLUSIONS: These findings suggest BG10 has anti-dermatitic activity through inhibiting activation of macrophages. Therefore, such effects of BG10 may provide information for the application of aged black garlic for prevention and therapy of contact dermatitis.